A study on the reinsurance industry of the Philippines for the period 1996-2001 - Limchua, Kent L. (Animo Repository, 2002)
According to the Standard Industry Classification System (SICS), the reinsurance industry is composed of establishments primarily engaged in assuming all or part of the risk associated with existing insurance policies originally underwritten by other insurance. This study aims to assess the performance of the reinsurance industry in the Philippines from 1996-2001. The study will present the current condition of the industry, the problems it faces and the factors that affect it. Certain factors and problems hinder the growth of the reinsurance industry. The state of the economy is one factor that affects the growth of the industry. Reinsurance reflects the condition of the economy--if the economy is weak and sluggish, the earnings of the industry are small and there is very little growth. Financially, the professional reinsurance companies in the country lack sufficient capitalization which prevents them from assuming large risks and this in turn results to the flight of a significant portion of reinsurance business to other countries. Professional reinsurance companies also face the problem in management. Underwriters and actuaries are limited and not many people are interested in pursuing a career in insurance. The Insurance Code of 1978 is also a cause of some problems for the industry. Finally, the September 11 terrorist attack on the World Trade Center has caused premium rates to increase significantly. The attack has also made reinsurers more cautious. The industry has potential to achieve a high growth rate and it is very profitable. If the global and Philippine economy improves then the reinsurance industry would pick up as well. There might be a slight improvement in the industry because export figure have gone up, vehicle sales increased slightly, more aviation and passenger insurance has been purchased, etc. The reinsurance industry is profitable but it entails a large amount of capital and risk. In the Philippines particularly, there has only been a small amount of reinsurance claims so the profits are greater than the cost and expenses. It is an industry which very few know about and understand yet it is an industry that if all factors and aspects are managed properly can be financially rewarding reinsurance business changed over the years as the number of insurance companies grew and the volume and size of risks written increased. The increase in demand has also led to the expansion of reinsurance coverage to practically all the aspects of the current insurance market. In the Philippines, the first domestic professional reinsurer was established only in the late 1950's. Before then, domestic insurance companies would place their reinsurance with British insurance companies and foreign professional reinsurers. The Reinsurance Company of the Orient was established in 1956 and was followed by the Philippine Reinsurance Corporation in 1958. In 1963 the Eastern General Reinsurance Company was organized.